2013
DOI: 10.1007/s00259-013-2521-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 18F-FDG PET/CT for assessing response to radiofrequency ablation treatment in lung metastases: a multicentre prospective study

Abstract: The specificity of PET/CT at 3 months is low because of persistent inflammation, especially when the lesion is close to the pleura. This technique is useful for its negative predictive value, but positive findings need to be confirmed by histology before new treatment is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 32 publications
1
17
1
Order By: Relevance
“…Deandreis et al reported that FDG-PET could detect LTP at the treatment site with more sensitivity than conventional CT [16]. On the other hand, Bonichon et al reported low specificity and a high false-positive rate using evaluation with FDG-PET/CT 3 months after RF ablation [15]. The authors also asserted that FDG-PET/CT was useful for its negative predictive value.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Deandreis et al reported that FDG-PET could detect LTP at the treatment site with more sensitivity than conventional CT [16]. On the other hand, Bonichon et al reported low specificity and a high false-positive rate using evaluation with FDG-PET/CT 3 months after RF ablation [15]. The authors also asserted that FDG-PET/CT was useful for its negative predictive value.…”
Section: Discussionmentioning
confidence: 95%
“…The primary endpoint of the current study was thus determined as described in these prior reports. Several clinical trials conducted more recently have evaluated the utility of FDG-PET as an evaluation method for RF ablation of lung tumors [11,15]. Deandreis et al reported that FDG-PET could detect LTP at the treatment site with more sensitivity than conventional CT [16].…”
Section: Discussionmentioning
confidence: 99%
“…moderate to high 18 F-FDG uptake might persist. However, this does not indicate progression on follow-up in the majority of cases [68]. As the ablation zone undergoes fibrous transformation and shrinks, the ring-like uptake pattern that can still be present at 6 months will be replaced by a nodular pattern.…”
Section: Pet/ctmentioning
confidence: 90%
“…5) [66]. Three months after treatment, 57 -68 % of the ablation zones will show no or mild 18 F-FDG uptake which has a high negative predictive value [67,68]. In the remaining cases, a ▶ Fig.…”
Section: Pet/ctmentioning
confidence: 99%
See 1 more Smart Citation